Calvinist Theology and the Foundations of Modern Civil Society - ZHANG, Sheng (Journal of Research for Christianity in China (JRCC), 2025)
The Puritans built the strongest bulwark for human liberty through “freedom of conscience.” Grounded in this principle, they developed a comprehensive concept of liberty imbued with Christian individualism, encompassing virtually all elements of modern civil society. Simultaneously, through the framework of “covenant theology,” they developed a comprehensive system of socio-political, lifestyle, and cultural principles, establishing the following elements constituting modern civil society: the state and its people must enter into a covenant; governmental authority derives from the people’s authorization and agreement, embodied in the constitution; separation of church and state alongside religious tolerance; a widespread awareness of contractual obligations and the rule of law within society; representative government; and individual civil rights. These very foundations form the bedrock of modern civil society.